2015
DOI: 10.1111/ojoa.12064
|View full text |Cite
|
Sign up to set email alerts
|

Collapsing Commodities or Lavish Offerings? Understanding Massive Metalwork Deposition at Langton Matravers, Dorset During the Bronze Age–Iron Age Transition

Abstract: The discovery of 373 intact and broken tin-bronze socketed axes accompanied by 404 fragments in four pits at Langton Matravers collectively represents one of the largest hoards found to date in prehistoric Britain and Ireland. They were very probably never meant to be used as axes as the very high levels of tin they contain would have made them brittle. Many were poorly finished, with the majority still containing their casting cores. The axes are typologically dated to the Llyn Fawr metalwork phase (c.800-600… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…19; Roberts et al . 2015). This includes three sites in Yorkshire, although none is entirely unproblematic in terms of the dating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19; Roberts et al . 2015). This includes three sites in Yorkshire, although none is entirely unproblematic in terms of the dating.…”
Section: Discussionmentioning
confidence: 99%
“…(Cronyn 1992, 184). There are a small number of iron objects that have been found primarily in southern and eastern England such as socketed axes, socketed spearheads, a rivet and a sword which, whilst frequently lacking archaeological contexts, appear to be typological imitations of Late Bronze Age-Earliest Iron Age forms (Collard et al 2006, Table 6, Fig 19;Roberts et al 2015). This includes three sites in Yorkshire, although none are entirely unproblematic in terms of the dating.…”
Section: The Wool Textilementioning
confidence: 99%
“…Large hoards of fullsized and miniature Armorican-type axeheads deposited as-cast in north-west France (and to a lesser extent in southern Britain), for instance, have been broadly interpreted as ingots rather than functional tools (Briard 1965: 241-82). However, the value of socketed axeheads was clearly changing at this time, with forms sometimes manufactured in iron and high tin-bronze alloys (Manning & Saunders 1972;Roberts et al 2015). Rather than functioning economically or as utilitarian items, many of these Earliest Iron Age axeheads appear to be symbolic tokens designed solely for consumptive depositional activities (Roberts et al 2015;Fontijn 2019: 98-103).…”
Section: Scaling Down: Functionality and Miniaturisation Small Axehea...mentioning
confidence: 99%
“…The axe is extensively decorated and the blade has been removed following the pattern of the decoration (see Figure 5). Bluntness can be cautiously interpreted as a sign of use (an axe could be deposited without ever being sharpened -see for example axes from Langton Matravers (Roberts et al 2015)), especially if observed in conjunction with other indicators. Sharpness, however, cannot be interpreted as a sign of no use as it is more than possible to re-sharped a blade, following use and erase earlier use marks.…”
Section: Use Marks -Bladementioning
confidence: 99%